Acute and Chronic Effects of SGLT2 Inhibitor Empagliflozin on Renal Oxygenation and Blood Pressure Control in Nondiabetic Normotensive Subjects: A Randomized, Placebo‐Controlled Trial. Issue 13 (7th July 2020) - Zanchi, Anne; Burnier, Michel; Muller, Marie‐Eve; Ghajarzadeh‐Wurzner, Arlène; Maillard, Marc; Loncle, Nicolas; Milani, Bastien; Dufour, Nathalie; Bonny, Olivier; Pruijm, Menno
Abstract : Background: The sodium/glucose cotransporter 2 inhibitor empagliflozin has cardiorenal protective properties through mechanisms beyond glucose control. In this study we assessed whether empagliflozin modifies renal oxygenation as a possible mechanism of renal protection, and determined the metabolic, renal, and hemodynamic effects of empagliflozin in nondiabetic subjects. Methods and Results: In this double‐blind, randomized, placebo‐controlled study, 45 healthy volunteers underwent blood and urine sampling, renal ultrasound, and blood‐oxygenation‐level–dependent magnetic resonance imaging before and 180 minutes after administration of 10 mg empagliflozin (n=30) or placebo (n=15). These examinations were repeated after 1 month of daily intake. Cortical and medullary renal oxygenation were not affected by the acute or chronic administration of empagliflozin, as determined by 148 renal blood‐oxygenation‐level–dependent magnetic resonance imaging examinations. Empagliflozin increased glucosuria (24‐hour glucosuria at 1 month: +50.1±16.3 g). The acute decrease in proximal sodium reabsorption, as determined by endogenous fractional excretion of lithium (−34.6% versus placebo), was compensated at 1 month by a rise in plasma renin activity (+28.6%) and aldosterone (+55.7%). The 24‐hour systolic and diastolic ambulatory blood pressures decreased significantly after 1 month of empagliflozin administration (−5.1 and −2.0 mm Hg, respectively). Serum uric acid levels decreased (−28.4%), hemoglobin increased (+1.7%), and erythropoietin remained the same. Conclusions: Empagliflozin has a rapid and significant effect on tubular function, with sustained glucosuria and transient natriuresis in nondiabetic normotensive subjects. These effects favor blood pressure reduction. No acute or sustained changes were found in renal cortical or medullary tissue oxygenation. It remains to be determined whether this is the case in nondiabetic or diabetic patients with congestive heart failure or kidney disease. REGISTRATION : URL: https://www.clini​caltr​ials.gov ; Unique identifier: NCT03093103 .